GAMBARAN TENTANG HASIL BELAJAR SISWA INTROVERT DI KELAS IV SEKOLAH DASAR - Rizal Taufik; Teguh Satria; Novia Sari Alfitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the learning outcomes of introvert students in the fourth grade of elementary school. The type of research used in this is a case study. The research subjects studied were from the findings of information with class teachers, namely introvert students' learning outcomes in the attitude aspect that is not visible during the learning process. Data collection using non-test instruments in the form of observations using checklists, was carried out to obtain data on learning outcomes in the learning process, then interviews were conducted with teachers and introvert students, supported by video documentation. The results of the study found that stimuli in the form of attention, guidance, and support from teachers succeeded in fostering motivation to participate in learning activities for introvert students. Both in terms of social interaction, courage to take risks, in terms of depth of thinking, as well as in aspects of students' attitudes towards the subject matter based on the narrative of inner impulses. In the aspect of students' attitudes towards values or norms related to the subject matter and in expressing feelings, introvert students do learning predominantly through writing, teachers provide opportunities for introvert students to be involved in learning with what introvert students do. Emotional support, support for appreciation, and support for information are important for introvert students in elementary school.